2014
DOI: 10.1534/g3.114.012989
|View full text |Cite
|
Sign up to set email alerts
|

Adult Plant Development in Triticale (× Triticosecale Wittmack) Is Controlled by Dynamic Genetic Patterns of Regulation

Abstract: Many biologically and agronomically important traits are dynamic and show temporal variation. In this study, we used triticale (× Triticosecale Wittmack) as a model crop to assess the genetic dynamics underlying phenotypic plasticity of adult plant development. To this end, a large mapping population with 647 doubled haploid lines derived from four partially connected families from crosses among six parents was scored for developmental stage at three different time points. Using genome-wide association mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…,b, , , Würschum et al. ,c). In brief, the study is based on a mapping population with 647 doubled haploid (DH) (Würschum et al.…”
Section: Methodsmentioning
confidence: 99%
“…,b, , , Würschum et al. ,c). In brief, the study is based on a mapping population with 647 doubled haploid (DH) (Würschum et al.…”
Section: Methodsmentioning
confidence: 99%
“…These and the vast majority of other QTL studies in plants assessed the expression of traits at a certain stage, frequently at final harvest or at the time point when a certain developmental stage such as flowering and kernel architecture has been reached (Buckler et al ., ; Hung et al ., ; Cook et al ., ). More recently, some studies have been reported on dynamically acting genetic factors in plants assessed via monitoring trait expression at multiple time points (Yan et al ., ; Bian et al ., ; Busemeyer et al ., ; Moore et al ., ; Liu et al ., ; Würschum et al ., ,b; Bac‐Molenaar et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the noncontact nature of the sensors, and their placement on vehicles capable of traversing research plots at a rapid pace, HTPP systems are capable of collecting vast amounts of data in an efficient manner ( Andrade-Sanchez et al 2014 ; White et al 2012 ; Busemeyer et al 2013 ). The ability to collect data rapidly also permits comprehensive assessment of crop development, and, with it, the ability to map QTL expression as a function of time, which is critical given that most traits of agronomic and economic importance are dynamic in nature ( Wu and Lin 2006 ; Würschum et al 2014 ). Despite awareness of this reality, the majority of QTL studies rely on phenotypic data collected at a single time point, offering only a final view of accumulated QTL effects.…”
mentioning
confidence: 99%